2019
DOI: 10.7759/cureus.5177
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy: Medical and Psychiatric Aspects. Role of Psychotropic Medications in the Treatment of Adults with “Broken Heart” Syndrome

Abstract: Takotsubo cardiomyopathy (TTC) is reversible stress-induced cardiomyopathy featuring symptoms of acute myocardial infarction without significant coronary artery abnormalities. TTC is frequently precipitated by stressful emotional events but it also has been reported as a result of substance withdrawal, non-cardiac events, and dangerous drug-to-drug interaction. The plasma levels of both epinephrine and norepinephrine were significantly elevated in TTC patients, suggesting that elevated catecholamine levels mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…This condition, also referred to as stress-induced cardiomyopathy, is distinguished by acute segmental ventricular dysfunction in a non-coronary distribution. It commonly occurs in reaction to severe emotional or physical stress and can cause significant clinical problems 7 . Patients have presentations mimicking acute coronary syndrome, with symptoms such as shortness of breath, hypotension, and chest pain.…”
Section: Covid-19: a Systemic Conditionmentioning
confidence: 99%
“…This condition, also referred to as stress-induced cardiomyopathy, is distinguished by acute segmental ventricular dysfunction in a non-coronary distribution. It commonly occurs in reaction to severe emotional or physical stress and can cause significant clinical problems 7 . Patients have presentations mimicking acute coronary syndrome, with symptoms such as shortness of breath, hypotension, and chest pain.…”
Section: Covid-19: a Systemic Conditionmentioning
confidence: 99%
“…However, it is well known that brain neurons that mediate vasoconstriction innervate coronary microcirculation, supports the concept that regional myocardial stunning among patients with TTS may be of neurogenic origin [22]. By the time, numerous studies demonstrated increased sympathetic activity, and consequent catecholamine excess, in TTS patients [27,36]. The higher epinephrine levels stimulate the β2-adrenoceptor coupling switch from membranous Gs to Gi proteins, with a consequent negative inotropic effect.…”
Section: Takotsubo and Anxiety Disorders: Pathophysiologic Connectionsmentioning
confidence: 86%
“…Nevertheless, it should also be considered that the survey was submitted during the hospital stay, possibly being influenced by hospitalization-related anxiety. Another case-control study based on 19 patients with TTS and sex-, age-, and residence-matched controls has shown that only major depressive disorder (MDD) had a significantly higher prevalence in Takotsubo patients than controls [27]. The main limitations of the previous two above studies were the small sample size.…”
Section: Psychiatric Disorder Tts (%) Stemi (%) Gp (%) P-valuementioning
confidence: 98%
“…Alcohol withdrawal has been associated with excess catecholamines releases from increased adrenergic activity, which can have a cardiomyotoxic effect [ 13 ] and there is increasing evidence that excess catecholamines can be responsible for TC [ 10 ]. Agu et al in their case report suspected that TC in patients with delirium tremens, which is a severe form of alcohol withdrawal syndrome, is possibly secondary to the cardiomyotoxic effect of catecholamines or CNS-medicated coronary spasm [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology is complex and not well understood. However, there is increasing evidence that excess catecholamines may be responsible for TC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%